Pengaruh Literasi Keuangan, Penggunaan E-Money dan Kontrol Diri Terhadap Perilaku Konsumtif pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas YPPI Rembang - Zia Ul Haq; Agustina Widodo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of financial literacy, e-money usage, and self-control on consumptive behavior among students at the Faculty of Economics and Business, YPPI University, Rembang. The method used in this study is quantitative. Data were collected through the distribution of a predetermined questionnaire using the proportionate stratified random sampling technique. The sample size in this study was 72 respondents who were students at the Faculty of Economics and Business and used the e-money platform. Data analysis used multiple linear regression with the help of SPSS. The results showed that financial literacy had a negative effect on consumptive behavior. This means that the higher the students' financial literacy, the lower their tendency to engage in consumptive behavior. The use of e-money had a negative effect on consumptive behavior. This means that students were more prudent and controlled in their use of e-money, so they did not engage in consumptive behavior. Self-control has a negative effect on consumptive behavior. This means that the better students' ability to control themselves, the lower their consumptive behavior.